Food and beverage industries' participation in health scientific events: considerations on conflicts of interest - Daniela S. Canella; Ana Paula B. Martins; Hugo F.R. Silva; Adriana Passanha; Bárbara H. Lourenço
Several sectors of the industry (pharmaceutical, food, and other) often occupy a prominent position in scientific meetings on health. The aim of this article is to discuss the participation of food and beverage industries (Big Food and Big Soda) in events organized by scientific institutions in health and nutrition, highlighting potential conflicts of interest in such partnerships. As an example, the authors report the case of a Brazilian national event organized by a nutrition scientific association in 2011. Focused on the theme "Evidence-based Nutrition," the event's scientific program was largely influenced by corporate sponsors. For example, a symposium at this congress was organized by a beverage company known worldwide for its sugar-sweetened products and classified as the "diamond sponsor" of the event. While debating the adoption of healthy lifestyles in the current scenario of rising occurrence of obesity, the rationale for health promotion was reduced to providing information that would motivate rational individual choices, thus ignoring any political, economic, cultural, marketing, and social factors involved in the global process of nutrition transition. The authors conclude that conflicts of interest are present in the participation of food and beverage industries in health scientific events. The industries' strategy attempts to grant legitimacy to the production and marketing of their products through an association with adequate health practices. Health professionals and policy-makers should reflect on such partnerships because their main purpose is to generate profit, not the promotion of public health.